No, either or both parents with metabolic syndrome: comparative study of its impact on sons and daughters - Park, Jun-Hong; Cho, Min Hyung; Lee, Hae Sang; Shim, Young Suk (Frontiers in Endocrinology, 2025)
BackgroundMetabolic syndrome (MetS) is known to have parental influence on children’s metabolic health, increasing the risk for the cardiometabolic diseases. However, the extent of the association and its sex-specific differences remain unclear.ObjectiveThis retrospective, comparative study aimed to investigate the influence of parental MetS on their offspring, utilizing data from the Korea National Health and Nutritional Examination Survey.MethodsThe study population was narrowed to 5,245 participants. Each sex was further divided into three groups: children with neither parent having MetS were labeled as “No,” those with only one affected parent was labeled as “Either,” and those with both parents affected were labeled as “Both.” Analysis of covariance and multiple regression analysis were used to compare the cardiometabolic risk factors among the three groups.ResultsChildren with one or both parents affected by MetS had significantly higher waist circumference, blood pressure, triglycerides, and fasting glucose levels. These associations were more profound in boys than in girls.ConclusionMetabolic risk factors were more strongly associated with parental MetS in boys than in girls. The number of parental MetS cases appeared to have a proportional impact on metabolic components in boys, unlike the variable results observed in girls. These results emphasize the need for targeted interventions in families with a history of MetS.